IDENTIFICATION OF EFFECTIVENESS OF CENTELLA ASIATICA LEAVES AS AN ALTERNATIVE APPROACH TO MANAGING PHYSIOLOGICAL AND PSYCHOLOGICAL CHANGES IN MENOPAUSE : DESCRIPTIVE INITIAL STUDY - Fitria, Irma; Agustina, Agustina; Hanum, Zulfa (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: Menopause represents a significant health issue affecting millions of women globally, with 75-85% experiencing disruptive symptoms such as hot flashes, sleep disturbances, mood changes, and increased risks of osteoporosis and cardiovascular disease. Centella asiatica contains phytoestrogens and antioxidants that may substitute for estrogen function in the body and help reduce physiological and psychological symptoms during menopause. This study aims to evaluate the effectiveness of Centella asiatica in reducing physiological and psychological symptoms during menopause. Method: This study employed a descriptive design. Data were collected cross-sectionally from 85 respondents experiencing physiological and psychological changes associated with menopause, residing in Bireuen District and distributed across 18 community health center service areas. Data collection was conducted from July to September 2025, through random sampling. Data were collected by distributing questionnaires to determine menopausal women understanding of centella asiatica and its effectiveness in reducing menopausal symptoms. Results: Centella asiatica was found to be effective in alleviating both physiological and psychological changes in menopause. Centella asiatica was found to be effective in alleviating various physiological changes associated with menopause. Specifically, it improved skin health and reduced aging-related problems (64.7%), enhanced blood circulation (62.3%), supported cognitive function (51.7%), alleviated bone-related problems (88.2%), and reduced sleep disturbances or insomnia (73.0%). In addition to alleviating physiological changes during menopause, Centella asiatica was also effective in reducing psychological symptoms, particularly by decreasing anxiety and stress (68.2%) commonly experienced by women during this transitional period. Conclusion: Centella asiatica demonstrates effectiveness in mitigating physiological and psychological changes during menopause, and thus may serve as an alternative solution to reduce menopausal symptoms.